Identities and bases in the hypoplactic monoid - Cain, Alan J. (2022)
This work is funded by National Funds through the FCT - Fundacao para a Ciencia e a Tecnologia, I.P., under the scope of the project UIDB/00297/2020 (Center for Mathematics and Applications) and the project PTDC/MAT-PUR/31174/2017. The third author is funded by National Funds through the FCT - Fundacao para a Ciencia e a Tecnologia, I.P., under the scope of the studentship SFRH/BD/138949/2018.